Little effect of training in the heat on cycling performance at normal temperature - Morrison, J. P.; Hopkins, W. G.; Sleivert, G. G. (Sportscience, 2002)
In a randomized crossover study of the effect of adaptation to exercise in the heat on endurance performance at room temperature, nine highly-trained male cyclists performed a simulated 40-km time trial at 20°C on an air-braked ergometer, preceded by 7 d of self-selected training on a cycle ergometer in the heat (90 min.d-1 at 37°C and 50% humidity) or 7 d of control training (90 min.d-1 at 20°C and 50% humidity) at similar perceived effort. A 2-wk washout period separated these acclimation periods, during which athletes replicated training recorded in the two weeks before their first acclimation period. The measures of acclimation were changes in heart rate, core temperature, whole-body sweat rate, and perceived exertion during a ride at fixed intensity on the first and last day of each acclimation period; an additional measure was the hematocrit on the day after each acclimation period. The observed mean effect of training in the heat on performance time in the 40-km time trial was 0.4% (95% confidence interval -1.5 to 2.2%). The chances that the true effect on performance is beneficial/trivial/harmful are 35/54/11%. Only onethird of the cyclists showed substantial changes in perceived exertion and heart rate consistent with heat acclimation, and the individual differences in heat acclimation did not relate consistently to performance in the time trial. In conclusion, moderately intense training in the heat produced only modest variable heat acclimation and only the possibility of a worthwhile enhancement of performance. Highly trained individuals probably need a more marked stimulus to achieve substantial heat adaptation and effects on performance.